Feasibility and challenges of Recirculating Aquaculture Systems (RAS) in rainbow trout (Oncorhynchus mykiss) post-smolt production in the coastal subarctic Finland - Sinisalo, Kalle, 1990- (2020)
Verkefnið er lokað til 28.05.2021. Due to the strict national environmental legislation and as a mitigation measure for aquaculture nutrient emissions, the Finnish National Aquaculture Location Management Plan (NALMP) is pushing rainbow trout aquaculture production in offshore units. The coast, however, has only a limited smolt production capacity with hardly any growth prospects with traditional cultivation methods. The situation has created high demand for post-smolt that can eventually be cultivated to slaughter size during the short subarctic growth season. This study aims to determine how seasonality challenges and affect the feasibility of recirculating aquaculture systems (RAS) in rainbow trout (Oncorhynchus mykiss) post-smolt production in the northernmost coast of Finland. Through a comprehensive literature review and aquaculture expert interviews, challenges in RAS post-smolt production were identified. Based on the findings, different post-smolt production scenarios were created to combine RAS post-smolt production with offshore open net pen food fish production. The production planning was based on a unique growth model developed specifically for rainbow trout by the Author. Finally, a feasibility analysis was executed for different production scenarios. The results indicate that cultivating rainbow trout post-smolt in a recirculating aquaculture system can be economically feasible in Finland. Self-cultivated RAS post-smolt can not only decrease the post-smolt cost but can also provide better smolt delivery reliability and time savings for the offshore operator. Additionally, a RAS facility can lower the nutrient emissions from the post-smolt production and provide food fish for summer markets when there is scarcity of cultured fish. Further research is required to identify proper acclimatization methods before transferring post-smolt form RAS to sea. Additionally, further research endeavours should be focused on validating and verifying the growth model determined in this thesis as well as ...